PENGARUH AKUNTABILITAS PENGELOLAAN KEUANGAN DANA DESA, KEBIJAKAN DESA DAN PARTISIPASI MASYARAKAT TERHADAP KESEJAHTERAAN MASYARAKAT DESA DEMANGAN, KECAMATAN SAMBI, KABUPATEN BOYOLALI - Fentina Budi Nestiti; Suhesti Ningsih; Wikan Budi Utami (ITB AAS INDONESIA, 2022)
Abstract This study aims to determine the effect of accountability in the financial management of village funds, village policies and community participation on community welfare. This type of research uses quantitative research. The population used is the Village Apparatus, Village Consultative Body (BPD), Village Apparatus and the community in Demangan Village with the number of samples used in this study as many as 100 respondents. This research uses purposive sampling method. The data used in this study is primary data in the form of a questionnaire which will be processed using SPSS software version 23.0. The results of the analysis used in this study is Multiple Linear Regression Analysis. The results of the research that have been carried out show that partially village policies and community participation have a positive and significant effect on community welfare. As for the accountability of the financial management of village funds, it does not affect the welfare of the community. Keywords : Village Fund Financial Management Accountability, Village Policy, Community Participation and Community Welfare.